1989
DOI: 10.1002/bio.1170030103
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐flow bioluminescent dtermination of ATP in platelets using firefly luciferase immobilized on epoxy methacrylate

Abstract: Firefly luciferase was immobilized on epoxy methacrylate beads and used for a continuous-flow assay of ATP extracted from platelets. The immobilized luciferase had a half-life of 3 days at 25 degrees C; there was a 25% recovery of luciferase activity upon immobilization, and ca 50 reactors were made from 1 mg of commercial enzyme. The sensitivity of the assay was 0.3 pmol of ATP, and the response was linear between 1 and 500 pmol of ATP. The ATP content of platelets obtained with the present method correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Carrea et al showed decreased K M(ATP) (51-22 mmol/L) and increased K M(luciferin) (2.4-28 mmol/L) for FL immobilized on nylon (7). A similar change was found on epoxy methacrylate polymer (8). K M values for collagen-bound FL (24 and 11 mmol/L for ATP and luciferin, respectively) showed no difference from the free enzyme under mechanical stirring (26).…”
Section: Kinetic Constants Of Bccp-flmentioning
confidence: 86%
See 2 more Smart Citations
“…Carrea et al showed decreased K M(ATP) (51-22 mmol/L) and increased K M(luciferin) (2.4-28 mmol/L) for FL immobilized on nylon (7). A similar change was found on epoxy methacrylate polymer (8). K M values for collagen-bound FL (24 and 11 mmol/L for ATP and luciferin, respectively) showed no difference from the free enzyme under mechanical stirring (26).…”
Section: Kinetic Constants Of Bccp-flmentioning
confidence: 86%
“…The generally accepted K M(ATP) and K M(luciferin) for Photinus pyralis FL are in the ranges 25-250 and 2-10 mmol/L, respectively (7,8,(21)(22)(23)(24). Table 1 shows the K M and k cat values for both immobilized and free BCCP-luciferase calculated using Leonora software (25).…”
Section: Kinetic Constants Of Bccp-flmentioning
confidence: 99%
See 1 more Smart Citation
“…which was then positioned inside the luminometer in front of the photomultiplier window (Carrea et al, 1989).…”
Section: Methacrylate Reactor Preparationmentioning
confidence: 99%
“…We previously described bioluminescent flow systems using immobilized luciferase for ATP and ADP determination in platelets after extraction with ethanoCEDTA (Carrea et al, 1986;Carrea et al, 1989). The aim of this work was to improve a method for bioluminescence determination of ATP concentrations in platelets and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%